Outcomes of Cytoreductive Radical Prostatectomy for Oligometastatic Prostate Cancer on Prostate-specific Membrane Antigen Positron Emission Tomography: Results of a Multicenter European Study - Rajwa, Pawel; Robesti, Daniele; Chaloupka, Michael; Zattoni, Fabio; Giesen, Alexander; Huebner, Nicolai A; Krzywon, Aleksandra; Miszczyk, Marcin; Moll, Matthias; Stando, Rafał; Cisero, Edoardo; Semko, Sofiya; et al. (European urology oncology, 2024)
BACKGROUND: De novo oligometastatic prostate cancer (omPCa) on prostate-specific membrane antigen (PSMA) positron emission tomography (PET) is a new disease entity and its optimal management remains unknown. OBJECTIVE: To analyze the outcomes of patients treated with cytoreductive radical prostatectomy (cRP) for omPCa on PSMA-PET. DESIGN, SETTING, AND PARTICIPANTS: Overall, 116 patients treated with cRP at 13 European centers were identified. Oligometastatic PCa was defined as miM1a and/or miM1b with five or fewer osseous metastases and/or miM1c with three or fewer lung lesions on PSMA-PET. INTERVENTION: Cytoreductive radical prostatectomy. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: Thirty-day complications according to Clavien-Dindo, continence rates, time to castration-resistant PCa (CRPC), and overall survival (OS) were analyzed. RESULTS AND LIMITATIONS: Overall, 95 (82%) patients had miM1b, 18 (16%) miM1a, and three (2.6%) miM1c omPCa. The median prebiopsy prostate-specific antigen was 14 ng/ml, and 102 (88%) men had biopsy grade group ≥3 PCa. The median number of metastases on PSMA-PET was 2; 38 (33%), 29 (25%), and 49 (42%) patients had one, two, and three or more distant positive lesions. A total of 70 (60%) men received neoadjuvant systemic therapy, and 37 (32%) underwent metastasis-directed therapy. Any and Clavien-Dindo grade ≥3 complications occurred in 36 (31%) and six (5%) patients, respectively. At a median follow-up of 27 mo, 19 (16%) patients developed CRPC and eight (7%) patients died. The 1-yr urinary continence rate was 82%. The 2-yr CRPC-free survival and OS were 85.8% (95% confidence interval [CI] 78.5-93.7%) and 98.9% (95% CI 96.8-100%), respectively. The limitations include retrospective design and short-term follow-up. CONCLUSIONS: Cytoreductive radical prostatectomy is a safe and feasible treatment option in patients with de novo omPCa on PSMA-PET. Despite overall favorable oncologic outcomes, some of these patients have a non-negligible risk of early progression and thus should be considered for multimodal therapy. PATIENT SUMMARY: We found that patients treated at expert centers with surgery for prostate cancer, with a limited number of metastases detected using novel molecular imaging, have favorable short-term survival, functional results, and acceptable rates of complications.
Keywords: výsledek terapie; Neoplasm Metastasis; Male; Oligometastatic; retrospektivní studie; antigeny povrchové; glutamátkarboxypeptidasa II; Multimodal therapy; Positron-Emission Tomography; Europe; pozitronová emisní tomografie; Prostatic Neoplasms; Aged; Glutamate Carboxypeptidase II; mužské pohlaví; senioři; prostatektomie; Cytoreductive radical prostatectomy; Treatment Outcome; Evropa; prostatický specifický antigen; lidé; Humans; Prostate cancer; nádory prostaty; Antigens, Surface; cytoredukční chirurgie; Prostatectomy; Retrospective Studies; Prostate-specific membrane antigen positron emission tomography; metastázy nádorů; Cytoreduction Surgical Procedures; lidé středního věku; Prostate-Specific Antigen; Middle Aged